Effect of Random Distribution of Initial Imperfection Curvature on The Bearing Capacity of Double -Layer Flat Grids With Different Configurations - Arash Bayat; Hamidreza Ashrafi (مدل‌سازی پیشرفته در مهندسی عمران, 2024)
Space frame structures have recently received significant attention for covering large spaces due to their high degree of indeterminacy, considerable stiffness, and low weight. The existence of various imperfections in these structures, whether during material production or construction, is inevitable given the large number of members and nodes. Studies on these structures have shown their sensitivity to the presence of various imperfections, which have a stochastic nature. The main objective of this research is to investigate the effect of initial member curvature on the load-bearing capacity and reliability of flat two-layer grid structures with different patterns. For this purpose, two types of grid patterns, namely, orthogonal and skewed, with and without openings, were evaluated, resulting in a total of eight different structures. For each structure, the initial curvature of the members was randomly assigned using a normal distribution, and then a nonlinear incremental load analysis was performed using the OpenSees software. This process was repeated 1,000 times for each structure, resulting in a total of 8,000 nonlinear analyses. Finally, the statistical parameters and reliability of each structure were evaluated using the Monte Carlo method. The results show that the flat two-layer grid structure with an orthogonal pattern and without openings has better performance, with not only a higher average vertical load-bearing capacity and reliability but also lower sensitivity to initial member curvature.